Clinical characteristics and outcomes on discharge of women admitted to a Medium Secure Unit over a 4-year period. (March 2015) - Ribeiro, Rafael Bernardon; Tully, John; Fotiadou, Maria
Abstract: There are limited data on women in Medium Secure settings. This study aimed to address this by assessing the characteristics of 45 consecutive admissions to the female ward of a Medium Secure Unit in the United Kingdom over a four-year period. Data on demographics, clinical outcomes and from HONOS-Secure/HONOS and HCR-20 assessments were prospectively collected. Psychiatric diagnoses were recorded using ICD-10 criteria. Data on quality of life from WHO-QoL-BREF surveys were analysed. There was a high proportion of ethnic minorities (57.8%), high rates of childhood and adult abuse and low socioeconomic status. 62.2% of the patients had schizophrenia, 57.8% had multiple diagnoses. The median length of stay at discharge was 465.5 days. There were statistically significant reductions in rates of self-harm and HoNOS-Secure/HoNOS and HCR-20 scores following intervention. Scores on WHO-QoL-BREF compared favourably to a large-scale sample with mental health difficulties. Many characteristics of this sample were comparable to samples from similar populations. However the particularly high proportion of ethnic minorities suggested that the profile of our patients differs from nationwide samples. Intervention by our service was associated with reduced self-harm and improvements in well-defined clinical outcomes and quality of life measures using validated scales.